Dynamic Effect of Inflation Shocks in Sierra Leone: An Empirical Analysis - JACKSON, Emerson Abraham; TAMUKE, Edmund; JABBIE, Mohamed (Journal of Advanced Studies in Finance; Vol 10 No 2 (2019): JASF Volume X Issue 2(20) Winter 2019, 2020)
In this paper, we have utilized combination of econometric methodologies (Granger Causality and Autoregressive technique) to study the dynamic effects of inflation shocks in Sierra Leone, with 2007M01-2012019M03 as the scoping period. The objectives which include an examination of the existence of cointegration between CPI and other macroeconomic variables, determination of short and long run relationships and the effects of shocks using Impulse Responses and Variance Decomposition were thoroughly addressed as part of the empirical findings. To start with, outcome from Johansen Cointegration test revealed no evidence of cointegration between the variables, while the ultimate use of unrestricted VAR methodology to assess the model’s use for economic policy prescription using impulse response and variance decomposition shows that, with the application of a five-period shock, inflation is likely to show a downward trend. The major outcome from this study shows signs of persistent supply-side inflation pressure, more so with exchange rate (NEXR) and imported petrol prices (Platt_Avg), which are exogenously determined. In order to deal with the issues practically, outcomes from the study have also avail salient recommended points aiding as short-term measures in addressing persistent inflation upturn and its ongoing expectations.